Pendekatan Profesionalisme dalam Proyek Keinsinyuran: Studi Kasus Smart Greenhouse Bertenaga Surya - Rizkiawan, M. Asep; Aisyah, Tita; Ramza, Harry (Fakultas Teknik Universitas Lampung, 2025)
This study explores engineering professionalism through the implementation of a smart greenhouse powered by a solar power system and PLC-based automation in an industrial area. By applying the principles of professionalism - such as integrity, technical competence, and social responsibility - this project demonstrates how engineers can design and operate energy-independent systems while maintaining work ethics and safety. The research method used a case study with the design of a 600 Wp solar power plant system, PLC programming, daily load measurements, and performance analysis. The results show that the PLTS system generates 2 kWh of energy per day, while the greenhouse load requirement is only around 1.5 kWh per day, indicating energy surplus and high efficiency. In addition, automatic control maintains temperature and humidity stability inside the greenhouse. The conclusion confirms that professionalism significantly contributes to the technical, operational, and safety success of the system and recommends the integration of professionalism in education and sustainable engineering practices.